(untitled) (Bangladesh Journal of Agriculture, 2023)
The present investigation was undertaken to determine the major yield contributing traits, their direct and indirect effect on yield through the correlation and path coefficient analyzing using kidney bean germplasms. The research was based on the evaluation of germplasms collected from Sylhet, Bandarban hilly regions and Bangladesh Agricultural Research Institute, considering seventeen yield and its contributing characters. The studies unraveled that yield per plant had highly significant positive correlation with number of leaves (0.83, 0.78), number of pods per plant (0.78, 0.73), pod length (0.86, 0.76), dry weight of pod (0.97, 0.90), number of seeds per pod (0.79, 0.72) at both genotypic and phenotypic correlation levels. However, it showed significant and negative association with pod diameter (-0.67) at the genotypic level. In path correlation analysis high positive direct effect was found in seed yield towards yield per hectare. While, it was recorded negligible positive indirect effect towards yield per hectare via, days to first flowering, days to maturity, plant height, number or pods per plant, petiole length, pod diameter, and number of seeds per pod. The overall results suggested that the yield contributing traits such as number of leaves, number of pods per plant, pod length, dry weight of pod, and number of seeds per pod, should be considered as selection index for improvement of the yield of kidney bean. Bangladesh J. Agri. 2023, 48(2): 39-53